Comparison of nonsurgical periodontal therapy with oral hygiene instruction alone for chronic periodontitis - Asad, M.; Aziz, A.W.A.; Raman, R.P.C.; Himratul-Aznita, W.H.; Ali, T.B.T.; Chinna, K.; Vaithilingam, R.D. (Nihon University School of Dentistry, 2017)
We evaluated changes in clinical variables and microbiological profiles of periodontopathogens among 56 patients with moderate to severe CP who were randomly assigned to oral hygiene instruction (OHI; n = 28) or nonsurgical periodontal treatment (NSPT; n = 28). Periodontal variables were assessed and subgingival plaque samples were obtained from deep pockets (>5 mm) at baseline and 3 months after treatment. Real-time polymerase chain reaction was used to quantify Actinobacillus actinomycetemcornitans, Tannerella forsythia, Porphyrotnonas gingivalis, and Prevotella intermedia. All clinical variables significantly improved in both groups. Improvements in gingival bleeding index (GBI), probing pocket depth (PPD), and periodontal attachment loss (PAL) were significantly greater at 3 months after treatment in the NSPT group. At baseline, the prevalences of all pathogens were high. Significant reductions in microbial count were observed for A. actinomycetemcomitans and T. forsythia (P <= 0.05) in the NSPT group. None of the improvements in clinical variables was associated with changes in microbiological profiles. At 3 months after treatment, NSPT was associated with significantly greater improvements in GBI, PPD, and PAL as compared with OHI. A. actinomycetemcomitans and T. forsythia counts were significantly lower in the NSPT group.